33.0k views
3 votes
Need help with these last two questions, tysm if you do :D

Need help with these last two questions, tysm if you do :D-example-1
Need help with these last two questions, tysm if you do :D-example-1
Need help with these last two questions, tysm if you do :D-example-2
User Jwize
by
4.7k points

1 Answer

1 vote

Answer:

D.

A. x ≤ 1

Explanation:

Well for the first question we need to simplify the inequality.

4x + 3 < x - 6

-x to both sides

3x + 3 < -6

-3 to both sides

3x < -9

Divide 3

x < -3

So if x is less than -3 than it goes to the left starting at -3.

So D. is the answer.

So to solve the floowing inequality we simplify, distribute, and combine like terms.

3(2x - 5) + 3 ≤ -2(x + 2)

6x - 15 + 3 ≤ -2x -4

6x -12 ≤ -2x - 4

8x - 12 ≤ -4

+12

8x ≤ 8

8/8

x ≤ 1

Hence the answer is A. x ≤ 1

User Dalelane
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.